A LITERATUR REVIEW: FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN PERAWAT TERHADAP PENCEGAHAN VENTILATOR ASSOCIATED PNEUMONIA (VAP) DI RUANG ICU - syahri, halimah (Masker Medika, 2021)
Abstract Background : Mechanical ventilation has an important role as a substitute for ventilation function for patients with impaired respiratory function. The use of invasive ventilators has several complications such as Ventilator Associated Pneumonia (VAP). Prevention of VAP can be done by means of a VAP bundle. The action was mostly carried out by nurses. Therefore have a good knowledge of how to prevent VAP. Purpose : To determine the factors related to nurses' knowledge about the prevention of Ventilator Associated Pneumonia (VAP) in the ICU. Methods : Literature Review in 2015-2020. Article searches were conducted using electronic databases such as Google Scholar, sciendirect and Researchgate to answer the purpose of writing. Search articles using keywords intensive care unit, prevention of VAP, and knowledge of nurse using indonesia and english. Results : There were nine (9) articles related to nurse’s knowledge to prevention is quite good, because the majority of respondents with 3 years of work experience, undergraduate education level, and average aged 20-35 years. Conclusion : Based on the result of 9 scientific articles, it can be concluded that the factors related to nurse’s knowledge of VAP prevention are education level, work experience, training, and age. While the factors that are not related to the knowledge of nurse on the prevention of VAP are work experience, education level, age, training and certificates. Keywords: Intensive Care Unit, Prevention of VAP, Nurse knowledge.